PENANAMAN KARAKTER SOPAN SANTUN SISWA DENGAN PENERAPAN UNGGAH-UNGGUH BAHASA JAWA DI MI MUHAMMADIYAH KLIWONAN - Maghfiroh, Meilani Nur; Abduh, Muhammad (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2024)
This study aims to identify what factors are the basis for the success of Javanese language uploads applied in MI Muhammadiyah Kliwonan. Qualitative case study methodology is applied in this study. MI Muhammadiyah Kliwonan students became research subjects with data collection methods through interviews and observations. In this study, data triangulation techniques were used for data validation, which included data reduction, data presentation, and conclusion drawing the findings of this study show that Javanese language uploads foster manners-oriented characters in MI Muhammadiyah Kliwonan is carried out by habituating to using fine Javanese language when learning and doing fun learning and teachers always set a good example. Schools should continue to teach Javanese and also provide training to teachers to help them deepen the subject. This is because there are still Javanese learning materials that use Indonesian and not all teachers are fluent in Javanese.